The Principal's Efforts in Building Brand Image and Competitiveness in MI Al Qodir Wage Taman Sidoarjo - Lutfi Firdausi; Prim Masrokan; Agus Eko Sujianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Establishing Islamic Education Institutions in this era of globalization is an opportunity to face the challenges of the times. Maintaining it is even more difficult to compete with other institutions. Challenges and competition come from internal and external institutions. Challenges and competition come from internal and external institutions. Building a good perspective for (Brand image) users of institutions is one of the inevitability in building and introducing transformative Islamic educational institutions to the community in order to increase the competitiveness of Islamic Education Institutions. Through descriptive qualitative research supported by data from the field at MI al Qodir Wage Taman Sidoarjo, it was obtained that efforts to build a brand image of transformative Islamic educational institutions can be done through; 1) Market Identification 2) Segmentation and Positioning, 3) Differentiation of Education Services, and 4) Services of Transformative Islamic Education Institutions. Meanwhile, to build a brand image, this Islamic educational institution implements the theory of the marketing mix known as the 7P formula, namely; Product, Price, Place, Promotion, People, Physichal Evendnce, and Process. Furthermore, to maximize the positive impact of brnad image, institutions need to pay attention to supporting factors, including; a) Product Attributes or values that accompany the product, and b) Consumer Benefits of excellence or benefits obtained by consumers.